(untitled) (Journal on Excellence in College Teaching, 2024)
When faced with unexpected and charged conversations about race, class, gender, and other social identities, faculty often seek a list a strategies for what to say or do. Yet numerous, sometimes contradictory, strategies for navigating these discussions already exist. This article explores the issue of how might faculty and/or the faculty developers who support them choose among these many approaches. The author offers the framework of engaged intentionality, an approach to inclusive teaching and learning, to both help faculty navigate these specific conversations and develop multifaceted, responsive, and authentic pedagogical practices. The article concludes with an approach for generating one’s own intentions.